A. Schopenhauer’s Philosophy of Art - Andrijauskas, Antanas (Problemos, 1990)
In the paper an attempt is made to reveal the originality of Schopenhauer’s philosophy of art and to determine its role in the turn of the ontologically orientated philosophy to aestheticism and irrationalism. A special attention is paid to the critical study of Schopenhauer’s teachings about art, genius, creative intuition, artistic process as well as to the revelation of the relations between the philosophy and oriental aesthetics. Finally, the impact of Schopenhauer’s philosophy of art upon the subsequent thinking and artistic practice is retraced.